The Knowledge Management Model to Support Academic Activities at SD Al-Imam Islamic School Cileungsi Using the Seci Approach - Bajsair, Faik; Pranoto, Gatot Tri (JISA(Jurnal Informatika dan Sains), 2023)
The absence of a processing model, knowledge storage due Knowledge in the form of notes, files, pictures and so on disappears because 17 teachers dump themselves and bring knowledge, files, notes that ever made. Allegedly with the creation of a processing model, knowledge-based storage a website with a SECI approach can provide a managed solution with good knowledge at SD Al-Imam Islamic school." In this study, the authors develop model knowledge management system that is in accordance with the conditions that exist in SD Al-Imam Islamic School, knowledge formation using the SECI model. From the results of testing the experimental system knowledge management system using the Technology Acceptance Model (TAM) method the average result is above 58%, which means that the respondent is in doubt about the application of the system tried the knowledge management system at SD Al-Imam Islamic School.